Refractive Surgery.??RETHINKING - Chaudhry, M. Lateef (Pakistan Journal of Ophthalmology, 2007)
The progress in laser refractive surgery has entered an interesting state of recommendations and practices. Reference to my editorial views in volume 22 number 4, October 2006 issue of P.J.O. about correction of the most prevalent refractive error “presbyopia”, it still remains the most difficult and enigmatic refractive error to be corrected by all the measures known so far including presbylasik monovision, scleral expanding procedures, conductive keratoplasty, LTK, refractive IOL’s etc. while correction of hyperopia more than +4D with laser refractive surgery is sill not being recommended.